The Great Canadian Recovery: The Impact of COVID-19 on Canada's Labour Market - Stephen R. G. Jones; Fabian Lange; W. Craig Riddell; Casey Warman (Institute of Labor Economics (IZA), 2022)
The Canadian labour market experienced a period of unprecedented turmoil following the onset of the COVID-19 pandemic. We analyze the main changes using standard labour force statistics and new data on job postings. Envisaging a phase of temporary severing of employment relationships followed by a phase of more standard labour market search and matching, we use stock and flow data to understand key developments. We find dramatic changes in employment, unemployment and labour market attachment in the first few months of the pandemic and a broad though gradual recovery through to the end of 2021.
Keywords: E24; E32; I3; I14; I18; J21; J23; J31; J63; 330; COVID-19; coronavirus; job loss; unemployment; employment; transition rates